A Computational Fluid Dynamics Model for a Water Vortex Power Plant as Platform for Etho- and Ecohydraulic Research - Dennis Powalla; Stefan Hoerner; Olivier Cleynen; Nadine Müller; Jürgen Stamm; Dominique Thévenin (Energies, 2021)
The objective of the present paper is to develop a validated numerical model of a water vortex power plant that serves as a digital twin for further studies such as assessments of the ethohydraulic characteristics or the performance of such devices. The reference for the validation process is a large-scale hydraulic installation equipped with a full-scale water vortex power plant prototype installed in Dresden (Germany), where flow field measurements were carried out using three-dimensional Acoustic Doppler Velocimetry. The numerical model was implemented within the software package Star-CCM+. The unsteady, two-phase flow was solved with the Reynolds-Averaged Navier–Stokes equations in a Eulerian Multiphase approach, deploying a Volume of Fluid method to describe the free-surface flow. Water level and flow velocities were systematically compared in key areas of the device, demonstrating that the simulation is in good agreement with experimental observations. Relative differences are limited to at most 4% regarding water height in the system, and even the much more challenging velocity fields are reproduced with typical relative errors of roughly 10%. This validates the ability of the model to model the challenging flow conditions found in a water vortex power plant, enabling subsequent studies of the characteristics of this power plant concerning fish migration.